Heterogeneous Vancomycin-Intermediate Staphylococcus aureus Uses the VraSR Regulatory System to Modulate Autophagy for Increased Intracellular Survival in Macrophage-Like Cell Line RAW264.7 - Dai, Yuanyuan; Gao, Caihong; Chen, Li; Chang, Wenjiao; Yu, Wenwei; Ma, Xiaoling; Li, Jiabin (Frontiers in Microbiology, 2019)
The VraSR two-component system is a vancomycin resistance-associated sensor/regulator that is upregulated in vancomycin-intermediate Staphylococcus aureus (VISA) and heterogeneous VISA (hVISA) strains. VISA/hVISA show reduced susceptibility to vancomycin and an increased ability to evade host immune responses, resulting in enhanced clinical persistence. However, the underlying mechanism remains unclear. Recent studies have reported that S. aureus strains have developed some strategies to survive within the host cell by using autophagy processes. In this study, we confirmed that clinical isolates with high vraR expression showed increased survival in murine macrophage-like RAW264.7 cells. We constructed isogenic vraSR deletion strain Mu3∆vraSR and vraSR-complemented strain Mu3∆vraSR-C to ascertain whether S. aureus uses the VraSR system to modulate autophagy for increasing intracellular survival in RAW264.7. Overall, the survival of Mu3ΔvraSR in RAW264.7 cells was reduced at all infection time points compared with that of the Mu3 wild-type strain. Mu3ΔvraSR-infected RAW264.7 cells also showed decreased transcription of autophagy-related genes Becn1 and Atg5, decreased LC3-II turnover and increased p62 degradation, and fewer visible punctate LC3 structures. In addition, we found that inhibition of autophagic flux significantly increased the survival of Mu3∆vraSR in RAW264.7 cells. Together, these results demonstrate that S. aureus uses the VraSR system to modulate host-cell autophagy processes for increasing its own survival within macrophages. Our study provides novel insights into the impact of VraSR on bacterial infection and will help to further elucidate the relationship between bacteria and the host immune response. Moreover, understanding the autophagic pathway in vraSR associated immunity has potentially important implications for preventing or treating VISA/hVISA infection.